Detrending Singapore’s GDP : Beveridge–Nelson approaches. - Han, Lu. (2010)
This project examines the business cycles of Singapore spanning 31 years from 1978 to 2008 using three detrending techniques: the Hodrick-Prescott (HP) filter, Beveridge-Nelson (BN) and multivariate BN decompositions. We compare and contrast the business cycles obtained from these different methods. Applying the HP filter as a benchmark, the results show that the multivariate BN decomposition is better suited to study Singapore business cycles, compared to the univariate BN decomposition.